f(x)=((x+1)(x-2))/(x^2 -5x +1)f(x)= (x2 − 1)(x^3 + 3x^2/x^2 + 2)
Follow Math Help Forum on Facebook and Google+
Originally Posted by henri f(x)=((x+1)(x-2))/(x^2 -5x +1)f(x)= (x2 − 1)(x^3 + 3x^2/x^2 + 2) Quotient Rule: y = f(x)/g(x) y' = [g(x) f '(x) - f(x) g'(x)]/ [g(x)]^2 in prob 1: do: y = ((x+1)(x-2))/(x^2 -5x +1) your f(x) is: (x+1)(x-2) or: (x^2 -x -2) your g(x) is: (x^2 -5x +1)
For 1 my answer is: (-14x +16x +9)/(x^2 -5x +1)^2 Is this Correct? For 2 my answer is: (2x^6 +4x^4 +6x^5 +4x +6x^3 -6x^2-6x)/(x^2 +2)^2
what is x2 on your 2nd problem
x^2 is the denominator because it has to be squared
Originally Posted by henri For 1 my answer is: (-14x +16x +9)/(x^2 -5x +1)^2 Is this Correct? For 2 my answer is: (2x^6 +4x^4 +6x^5 +4x +6x^3 -6x^2-6x)/(x^2 +2)^2 I got: y' = [(x^2 -5x +1)(x-1) - (x^2 -x -2)(x -5)] / [x^2 -5x +1]^2 y' = [(x^3 -6x^2 +6x -1) - (x^3 -6x^2 +3x +10)] / (x^2 -5x +1)^2 . . . i got [3x -11] / [x^2 -5x +1]^2
Originally Posted by henri f(x)=((x+1)(x-2))/(x^2 -5x +1)f(x)= (x2 − 1)(x^3 + 3x^2/x^2 + 2) what is x2 in f(x)= (x2 − 1)(x^3 + 3x^2/x^2 + 2)
why is the numerator's derivative x-1 instead of 2x-1 and the same for the denominator
Sorry for my error but the second one is (X^2 -1)(. . .)
Originally Posted by henri why is the numerator's derivative x-1 instead of 2x-1 and the same for the denominator wow, you are correct, thanks, sorry to try and confuse you
no problem thanks for all. by the way is there an easier way to put in mathematical symbols in this program? I see other posts with better formats.
prob 2: i got: y= [x^5 +3x^4 -x^3 -3x^2] / (x^2 +2) y'= [(x^2 +2)(5x^4 +12x^3 -3x^2 -6x) - (x^5 +3x^4 -x^3 -3x^2)(2x)] / (x^2 +2)^2 ..... = [3x^6 + 6x^5 + 9x^4 + 24x^3 - 6x^2 - 12x] / (x^2 +2)^2
not sure about the symbols. Im new to this site using it for stats help. Thought i would try one i knew how to do
View Tag Cloud